2021
DOI: 10.2147/rmhp.s289343
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Professionals’ Willingness and Preparedness to Work During COVID-19 in Selected Hospitals of Southwest Ethiopia

Abstract: Background Many healthcare professionals are dying of COVID-19 while trying to save others. The loss in the healthcare workforce due to sickness and absence will double the risk of a crisis. Identifying barriers of willingness to work during epidemics outbreak and preparedness of healthcare professionals is important to minimize the shortage of human power. Methods Facility-based cross-sectional study was conducted among healthcare professionals working in the selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…However, some gaps such as inadequate PPE and training for COVID-19 infection control were identified. In comparison with a study in Ethiopia, the participants who reported that they were prepared for COVID-19 were lower (59.5%) (20) than in our study. Health workers may feel a sense of preparedness to handle a pandemic when they are trained adequately and provided with the necessary PPE.…”
Section: Discussioncontrasting
confidence: 99%
“…However, some gaps such as inadequate PPE and training for COVID-19 infection control were identified. In comparison with a study in Ethiopia, the participants who reported that they were prepared for COVID-19 were lower (59.5%) (20) than in our study. Health workers may feel a sense of preparedness to handle a pandemic when they are trained adequately and provided with the necessary PPE.…”
Section: Discussioncontrasting
confidence: 99%
“…The study by Zhang et al ( 7 ), identified three organizational factors, namely “work support,” “personal support,” and “risk support,” which were negatively associated with anxiety, whereas “work support” and “personal support” predicted higher life satisfaction in HCWs. A study in Ethiopia reported that protection and support of the needs of HCWs is a crucial factor toward their engagement to work, and provision of optimal care to patients ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within a few weeks, social and work life changed. The healthcare sector was one of the most affected areas [ 1 3 ]. Pandemic plans were activated [ 4 ], and emergency measures were taken in hospitals and intensive care units to treat a large number of patients with COVID-19 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pandemic plans were activated [ 4 ], and emergency measures were taken in hospitals and intensive care units to treat a large number of patients with COVID-19 [ 5 ]. However, general practitioners (GPs) are often the first to have contact with potential patients with COVID-19 [ 3 , 6 ] and the majority of patients with COVID-19 –mostly with mild and moderate symptoms [ 7 , 8 ]–are treated in GP practices. Apart from the additional workload of treating patients with COVID-19, GPs have to maintain regular primary health care [ 2 , 3 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation